Postcolonial Spaces The Politics of Place in Contemporary Culture - Teverson, A.; Upstone, S.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
With essays from a range of geographies and bringing together influential scholars across a range of disciplines, this book focuses on the role of space in the study of the politics of contemporary postcolonial experience, engaging with the spectrum of postcolonial spatialities which play a significant role in defining global postcolonial culture.
Keywords: Literature .; Literature, Modern—20th century; Postcolonial/World Literature; Twentieth-Century Literature